MAKNA DAN MODEL KOMUNIKASI PEMBANGUNAN - Udi Rusadi (Jurnal Studi Komunikasi dan Media, 2014)
ABSTRACTThis article is a review towards the communication development theory and practices in Indonesia, to analyze on how the tendencies of the usage of the development model and how it should be. Through the literature study, it illustrates that the participatory development model apparently has not become the main strategy. The linear model through the  dissemination of information and innovation diffusion is still the dominant paradigm. The usage of Communication and Information Technology for development, which focuses more on the provision of infrastructure have not yet been supported by the participatory and continuous model of empowerment model. The Communication and Information Technology has already become the social transformation paradigm which provides opportunities to increase the development capacity more rapidly and effectively. Based on the paradigm, this analysis offers a convergence of communication development model which is hoped to be able to mobilize all resources collaboratively and optimally. Keywords : communication, development, model, technology, convergenceABSTRAKTulisan ini merupakan tinjauan terhadap konsep-konsep teoritik komunikasi pembangunan dan prakteknya di Indonesia, untuk menganalisis bagaimana kecenderungan model pembangunan yang digunakan dan model sebaiknya. Melalui kajian literatur, kajian ini menunjukan   bahwa model komunikasi pembangunan partisipatif tampaknya masih belum menjadi strategi utama. Model linier melalui diseminasi informasi dan difusi inovasi masih menjadi  paradigma dominan. Penggunaan TIK untuk pembangunan  lebih fokus pada penyediaan infrastruktur belum diikuti dengan  pemberdayaan dengan model partisipatif dan berkesimambungan. Teknologi komunikasi dan informasi sudah merupakan paradigma transformasi sosial yang menyediakan peluang peningkatan kapasitas pembangunan yang lebih cepat dan berkualitas. Berbasis paradigma tersebut kajian ini menawarkan model komunikasi pembangunan konvergensi yang diharapkan bisa menggerakkan semua sumberdaya secara kolaboratif dan optimal. Kata-kata Kunci : komunikasi, pembangunan, model, teknologi, konvergensi